Innovative Methods Of Management Of Educational Projects In Teaching Economic Sciences - Abdullayev, Axrorjon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes the impact of innovative methods of managing educational projects in teaching economic subjects — Agile, Scrum, Lean and Design Thinking — on the educational process. Based on UNESCO, PISA, World Bank and statistical data from the higher education system of Uzbekistan, the effectiveness of these approaches in forming economic thinking, analytical skills and practical competencies in students is substantiated. The results of the study show the relevance of innovative methods in the modernization of economic education.